Trajectory Stability in the Traveling Salesman Problem. (16th April 2018) - Sánchez, Sergio; Cocho, Germinal; Flores, Jorge; Gershenson, Carlos; Iñiguez, Gerardo; Pineda, Carlos
Abstract : Two generalizations of the traveling salesman problem in which sites change their position in time are presented. The way the rank of different trajectory lengths changes in time is studied using the rank diversity. We analyze the statistical properties of rank distributions and rank dynamics and give evidence that the shortest and longest trajectories are more predictable and robust to change, that is, more stable.